ANALISIS INDEKS KINERJA USAHA KECIL MENENGAH DI KOTA BOGOR - Ramdhani, Faisal; Hardjomidjojo, Hartrisari (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): Maret, 2019)
Small and Medium Enterprises (SMEs) is the locomotive of economic development of Indonesia. Within the framework of the national economy, SMEs have contributed to the recruitment of labor, the increase of Gross Domestic Product (GDP) as well as the increase of export value and national investment. In the vision and mission of Bogor city government, SMEs are expected to become the economic buffer of the city of Bogor in the face of free market competition. Currently there are 13.953 SMEs in the city of Bogor. Sustainability Index based on multi dimensional scaling can be used to measure the performance status of SMEs and formulate specific strategies that need to be done to improve their competitiveness. This research was conducted from dimension setting, attribute determination, attribute review, multidimentional scaling analysis, Monte Carlo and Leverage. The value of  Stress and R2 resulted  is less than 0.25 and more than 0.80 so that the data has good of fit. The Monte Carlo analysis results for all SMEs have been valid because it has sustainability index ratio with Monte Carlo index less than 5%.  The results show that the average sustainability index for SMEs in Bogor city is 49.8, which means that the city of Bogor is in sufficient condition (index value is below 50). The result also shows that ecological and economical factors are the important factors for increasing the performance of SMEs. The simulation results show that changes in related dimensions can increase the average value of the sustainability index to above 60 (good category). Key Words : Small and Medium Enterprises (SMEs), Sustainability Index, competitiveness, multi dimensional scaling .